Candidate proteomic biomarkers in systemic sclerosis discovered using mass-spectrometry: an update of a systematic review (2014-2020) - Bălănescu Paul; Bălănescu Anca; Bălănescu Eugenia; Băicuş Cristian (Sciendo, 2021)
Background. Systemic sclerosis (Ssc) is an autoimmune disease characterized by graduate cutaneous and tissue fibrosis development and irreversible fibroproliferative vascular changes.